Apparel Start-Up Business Develovment Strategy Through The Enrichment Program as an Implementation of Kampus Merdeka - Noviana, Rosita; Kinding, Dwi Putriana Nuramanah; Iswarini, Fanny; Fathin, Safira (School of Business, IPB University (SB-IPB), 2025)
Background: The apparel industry, often called the fashion sector, has a significant attraction for teenagers because it provides space to express themselves and create an identity through the clothes they wear. The independent campus program is an excellent opportunity for students interested in apparel to pioneer skills and experience directly in the business industry. Purpose: The study aims to formulate alternative strategies that can be applied as business development for the Millennial's Project, which operates in the apparel industry due to implementing the Independent Campus program. Design/methodology/approach: SWOT, IFE, EFE, and QSPM analysis determine the best alternative strategies in business activities. Data collection was done using interviews with two experts and six consumers.Result: From the interviews conducted, the IFE value was obtained at 2.551, and the EFE value was 3.364; from the IFE and EFE assessment results, the IE matrix is located in cell 2. The values that indicate the company in quadrant 2 mean that the start-up is in the growth and build phase. The most appropriate strategies used in this phase are market penetration, market development, and product development. This alternative strategy is a priority, as evidenced by the AS value of 67 and TAS of 5.562, compared to the scores of other alternative strategies. Conclusion: So, this study shows that the appropriate alternative strategy for the Millennial Project is the development of new products such as hoodies, pants, and more varied colors.Originality/value (State of the art): The originality of this study lies in integrating SWOT, IFE, EFE, and QSPM analyses to formulate data-driven business development strategies for startups in the apparel industry within the Independent Campus program. Keywords: apparel industry, IE Matrix, Kampus Merdeka, business development, start-up